2022
DOI: 10.3390/v14071487
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Humoral Immune Responses after Immunisation with Low Virulent African Swine Fever Virus in the Large White Inbred Babraham Line and Outbred Domestic Pigs

Abstract: African swine fever virus is currently present in all of the world’s continents apart from Antarctica, and efforts to control the disease are hampered by the lack of a commercially available vaccine. The Babraham large white pig is a highly inbred line that could represent a powerful tool to improve our understanding of the protective immune responses to this complex pathogen; however, previous studies indicated differential vaccine responses after the African swine fever virus challenge of inbred minipigs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(70 citation statements)
references
References 57 publications
6
38
0
Order By: Relevance
“…Nevertheless, in some studies, high numbers of IFN-γ-producing cells did not always correlate to animal survival after challenge, indicating that induction of IFN-γ-specific T cells is not a sufficient indicator of protection either when virulent challenges were carried out shortly after immunizations [ 80 , 81 , 82 ] or when they were performed long after immunizations [ 59 ], which suggests the existence of other mechanisms, although without excluding this one, that would be involved in the protection afforded by different ASFV attenuated isolates [ 20 , 21 , 22 , 83 ]. Adenovirus, alphavirus and vaccinia virus vectors have all been shown to induce effective ASFV antigen-specific responses.…”
Section: Circulating Levels Of Cytokines During Asfv Infection In Vivomentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, in some studies, high numbers of IFN-γ-producing cells did not always correlate to animal survival after challenge, indicating that induction of IFN-γ-specific T cells is not a sufficient indicator of protection either when virulent challenges were carried out shortly after immunizations [ 80 , 81 , 82 ] or when they were performed long after immunizations [ 59 ], which suggests the existence of other mechanisms, although without excluding this one, that would be involved in the protection afforded by different ASFV attenuated isolates [ 20 , 21 , 22 , 83 ]. Adenovirus, alphavirus and vaccinia virus vectors have all been shown to induce effective ASFV antigen-specific responses.…”
Section: Circulating Levels Of Cytokines During Asfv Infection In Vivomentioning
confidence: 99%
“…So far, few pioneering studies have been carried out. Phenotyping of ASFV-specific IFN-γ-producing cells in pigs after immunization with BeninΔMGF and OURT88/3 have been fully characterized [ 59 , 82 ]. In both studies, the authors observed that the source of IFN-γ in both immunized groups originated from different subsets of CD8 + T cells, mainly cytotoxic (CD8 high ) T cells, particularly double-positive memory (CD4 + CD8 + ) T cells, suggesting a possible role of these cells in protection.…”
Section: Circulating Levels Of Cytokines During Asfv Infection In Vivomentioning
confidence: 99%
See 3 more Smart Citations